Freud y la Biología: Una Reflexión Historiográfica Acerca de la Concepción de F. Sulloway sobre la Teoría Psicoanalítica - Christiansen Renaud, María (Acta Universitaria, 2008)
This article examines the central argument in Frank Sulloway´s impressive book Freud, Biologist of the Mind, published in 1979. Sulloway’s thesis made a notable contribution to the general increase in skepticism among American historians of psychoanalysis. Given their relevance as part of this process, a rigorous scrutiny of this author’s arguments is an indispensable task for the philosophy of science, to which end this article attempts to contribute to the epistemological analysis of the strengths and weaknesses embedded in Sulloway’s strong criticisms of the orthodox history of Freudian thought.